Trichomonas vaginalis Macrophage Migration Inhibitory Factor Mediates Parasite Survival during Nutrient Stress - Yi-Pei Chen (American Society for Microbiology, 2018)
ABSTRACT Trichomonas vaginalis is responsible for the most prevalent non-viral sexually transmitted disease worldwide, and yet the mechanisms used by this parasite to establish and maintain infection are poorly understood. We previously identified a T. vaginalis homologue (TvMIF) of a human cytokine, human macrophage migration inhibitory factor (huMIF). TvMIF mimics huMIF’s role in increasing cell growth and inhibiting apoptosis in human host cells. To interrogate a role of TvMIF in parasite survival during infection, we asked whether overexpression of TvMIF (TvMIF-OE) confers an advantage to the parasite under nutrient stress conditions by comparing the survival of TvMIF-OE parasites to that of empty vector (EV) parasites. We found that under conditions of serum starvation, overexpression of TvMIF resulted in increased parasite survival. Serum-starved parasites secrete 2.5-fold more intrinsic TvMIF than unstarved parasites, stimulating autocrine and paracrine signaling. Similarly, we observed that addition of recombinant TvMIF increased the survival of the parasites in the absence of serum. Recombinant huMIF likewise increased the parasite survival in the absence of serum, indicating that the parasite may use this host survival factor to resist its own death. Moreover, TvMIF-OE parasites were found to undergo significantly less apoptosis and reactive oxygen species (ROS) generation under conditions of serum starvation, consistent with increased survival being the result of blocking ROS-induced apoptosis. These studies demonstrated that a parasitic MIF enhances survival under adverse conditions and defined TvMIF and huMIF as conserved survival factors that exhibit cross talk in host-pathogen interactions. IMPORTANCE Macrophage migration inhibitory factor (MIF) is a conserved protein found in most eukaryotes which has been well characterized in mammals but poorly studied in other eukaryotes. The limited analyses of MIF proteins found in unicellular eukaryotes have focused exclusively on the effect of parasitic MIF on the mammalian host. This was the first study to assess the function of a parasite MIF in parasite biology. We demonstrate that the Trichomonas vaginalis MIF functions to suppress cell death induced by apoptosis, thereby enhancing parasite survival under adverse conditions. Our research reveals a conserved survival mechanism, shared by a parasite and its host, and indicates a role for a conserved protein in mediating cross talk in host-pathogen interactions.